2018
DOI: 10.18632/oncotarget.26307
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin-1/TI-VAMP SNAREs interact with Trk receptors and are required for neurotrophin-dependent outgrowth

Abstract: SNARE proteins are essential components of the machinery that regulates vesicle trafficking and exocytosis. Their role is critical for the membrane-fusion processes that occur during neurotransmitter release. However, research in the last decade has also unraveled the relevance of these proteins in membrane expansion and cytoskeletal rearrangements during developmental processes such as neuronal migration and growth cone extension and attraction. Neurotrophins are neurotrophic factors that are required for man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 80 publications
(98 reference statements)
0
13
0
Order By: Relevance
“…The accuracy of our model decreased somewhat at 3 DIV, suggesting additional parameters in membrane remodeling were not captured. Perhaps analogously, in vivo Vamp2 -/- neurons have a largely normal morphology, suggesting compensatory mechanisms such as membrane added via ER-PM contact sites or exocytosis mediated by other SNARE proteins like VAMP7 (Fuschini et al, 2018; Galli et al, 1998) participate in membrane remodeling.…”
Section: Discussionmentioning
confidence: 97%
“…The accuracy of our model decreased somewhat at 3 DIV, suggesting additional parameters in membrane remodeling were not captured. Perhaps analogously, in vivo Vamp2 -/- neurons have a largely normal morphology, suggesting compensatory mechanisms such as membrane added via ER-PM contact sites or exocytosis mediated by other SNARE proteins like VAMP7 (Fuschini et al, 2018; Galli et al, 1998) participate in membrane remodeling.…”
Section: Discussionmentioning
confidence: 97%
“…VAMP-2 function is required for repulsion to class III semaphorins (Zylbersztejn et al, 2012). We have previously described how Stx1 mediates ligand-dependent exocytosis and attraction to neurotrophic factors (Fuschini et al, 2018) and Netrin-1 (Cotrufo et al, 2012;Cotrufo et al, 2011) through the interaction with Trk receptors and DCC, respectively. Here we describe how Stx1 interacts directly with the repulsive Netrin-1 receptor UNC5.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the t-SNARE Stx1 interacts with the guidance receptor DCC (Cotrufo et al, 2012;Cotrufo et al, 2011) and the tropomyosinrelated kinase (TrkB) receptor (Fuschini et al, 2018), with these associations being necessary for the Netrin-1-dependent chemoattraction and neurotrophin-dependent outgrowth of axons, respectively. These results indicate that Stx1 regulates exocytosis and membrane retrieval in growth cones, and is required for Netrin-1-induced chemotropic guidance in vitro and in vivo (Ros et al, 2015).…”
Section: Unc5 Receptors Co-associate With Stx1 Both In Vitro and In Vivomentioning
confidence: 99%
“…We conclude that VAMP2-mediated fusion is the primary source of membrane addition in developing neurons and that manipulating exocytic frequency or mode alters neuronal growth. Perhaps analogously, in vivo Vamp2 À/À neurons have a largely normal morphology, suggesting compensatory mechanisms such as membrane added by endoplasmic reticulum (ER)-PM contact sites or exocytosis mediated by other SNARE proteins like VAMP7 (Fuschini et al, 2018;Galli et al, 1998) participate in remodeling.…”
Section: Exocytic Mode and Morphogenesismentioning
confidence: 99%